Experiences of Communication and Working During the Covid‐19 Pandemic Among Nursing Home Staff: A Qualitative Interview Study - Elisabet Eriksson; Katarina Hjelm (Nursing Open)
ABSTRACT Aim To describe nursing home care staff's experiences of encounters and communication with colleagues, residents and residents’ family members as well as their experiences during the Covid‐19 pandemic while working in a multicultural environment. Design A qualitative descriptive study. Methods Interviews with 17 care staff from nursing homes in Sweden were analysed using qualitative content analysis. Results Care staff reported different working experiences related to their possibility to prepare themselves, and some felt more supported than others by their managers. Feelings of pride were experienced when Covid‐19 infections were prevented. Overall, they received information about Covid‐19, but not initially. Acceptance of colleagues with limited Swedish language skills was reported, but frustration and impaired communication were common. Negative mental health effects from working with critically ill residents and taking care of the deceased were reported. Conclusion Employers did not provide care staff with sufficient information and support, and strategies are needed to maintain communication with and between care workers. Further support is needed to maintain care workers’ mental health and well‐being during critical working conditions. Implications for the Profession and/or Patient Care Nursing home management needs to implement clear structured tools for communicating essential information. These tools should take language skills into consideration. During pandemics, care workers must receive the support they need to maintain their mental health and well‐being. Patient or Public Contribution No patient or public contribution.